Silver Jubilee of HER2 targeting: a clinical success in breast cancer - Jianli Zhao; Ziyue Zhou; Phei Er Saw; Erwei Song (Journal of the National Cancer Center)
In the last century, scientists have discovered that when human epidermal growth factor receptor 2 (HER2) is overexpressed or amplified—found in approximately 15 %–20 % of breast cancer patients—it significantly increases the risk of tumor recurrence and metastasis. This crucial discovery has made anti-HER2 therapy a central focus in breast cancer research and treatment. HER2 protein overexpression, along with gene amplification or mutation, is commonly seen in breast cancer. Techniques like immunohistochemistry and fluorescence in situ hybridization are used to detect HER2 expression and amplification, categorizing tumors as having high, low, or no HER2 expression, and highlighting their heterogeneity. Monoclonal antibodies are well-established in treating breast cancers with a high HER2 expression, while antibody-drug conjugates have shown effectiveness in cases with a lower expression. Additionally, tyrosine kinase inhibitors and monoclonal antibodies optimized for antibody-dependent cellular cytotoxicity have expanded treatment options, allowing for effective therapies in breast cancers with lower HER2 expression levels. Even for tumors with HER2 mutations or low expressions, anti-HER2 therapies can still be effective. Newer treatments, like bispecific antibodies and vaccines, are being tested in clinical trials and are expected to play a significant role in treating breast cancers with different HER2 expression profiles. These advances have revolutionized neoadjuvant therapy, guiding postoperative and intensive treatment strategies based on how well the therapies work. However, challenges such as drug resistance, drug interactions, and the mechanisms of HER2-targeted therapies are closely linked to the tumor's immune microenvironment. As research continues, the complexity and diversity of HER2 as a target across various cancer types have become increasingly clear, presenting new challenges and driving innovation. Since the discovery of HER2 as a target, it has dramatically changed the landscape of breast cancer diagnosis, treatment, and prognosis. With more than two decades of development, the potential for further advances in HER2-targeted therapies continues to grow. This review aims to provide a comprehensive overview of current progress and future directions in HER2-targeted therapies for breast cancer and their clinical implications.